Synthesis of novel vitamin E-selenium antioxidants and study of their antiproliferative and apoptotic properties - Vraka, Panayiota S.; Rikkou, Maria P.; Drouza, Chryssoula; Odysseos, Andreani D.; Keramidas, Anastasios D. (My University, 2006)
Selenium and vitamin E are two antioxidants that have attracted great attention due to a strong synergism resulting in anti-cancer activity. Further, accumulated evidence supports the chemical form of selenium as an important factor in eliciting defined cellular responses. There is ample evidence that TNF-family-mediated mitochondrial apoptosis involves the production of reactive oxygen species (ROS). In order to elicit the apoptotic effect of both vitamin E and selenium it has been essential to counterbalance the reduction of ROS through structural modifications of these compounds. Herein, we report the synthesis and assessment of the antioxidant activity as well as the cancer cell growth inhibitory and apoptotic properties of novel vitamin E-selenium esters (such as α-tocopheryl selenyl diacetate). These compounds were designed to (a) provide a better understanding of vitamin E synergism with selenium, (b) enable the synthesis of antioxidants combining both selenium and vitamin E apoptotic activity, and (c) elucidate the mechanisms underlying the potent apoptotic effects of succinate esters. Antioxidant activity and free radical scavenging capacity were assessed by the glutathione peroxidase (GPx) catalytic activity assay and 2,2-diphenyl-1-picrylhydrazyl (DPPH) assay, respectively. Reactions of organic peroxides with the antioxidants were evaluated by NMR spectroscopy. Redox potentials were determined using cyclic voltammetry. While the novel esters retained the antioxidant activity of both selenium and vitamin E, they had significant antiproliferative and growth inhibitory effects on three prostate cancer cell lines (PC-3, DU-145, LNCaP) as measured by the trypan blue exclusion test and the crystal violet proliferation assay. These properties were tested against their thionyl analogues, succinate and phenylselenyl succinate vitamin E esters. DAPI staining of nuclei revealed features of apoptotic cell death such as apoptotic bodies, apoptotic rings and condensed chromatin in diacetate and succinated esters of vitamin E, an effect not observed in cells treated with the natural vitamin E derivatives or the selenodiacetic acid. Apoptotic cell death was further assessed by caspase-3 activation, as detected by the cleavage of the fluorogenic caspace-3 substrate, z-DEVD-AFC. The presence of selenium further enhanced the pro-apoptotic effect of these compounds, as reveled by both DNA fragmentation and caspase-3 activation. Generally these novel selenium esters have cell growth inhibitory and pro-apoptotic properties superior to those of succinate, thionyl diacetic and phenylselenyl succinate esters. These differences in the biological properties imply that the higher stability of novel vitamin E-selenium esters play a key role in the improvement of the bioavailability of selenium at cellular level.